2017
DOI: 10.4103/ijnmr.ijnmr_178_14
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preanesthetic parental presence on preoperative anxiety of children and their parents: A randomized clinical trial study in Iran

Abstract: Introduction:Parental presence during induction of anesthesia (PPIA) has been a controversial issue, with some studies showing its effects on reducing anxiety. Hence, this study aimed to investigate the effects of PPIA on preoperative anxiety of children as well as their parents.Materials and Methods:This clinical trial was conducted among 60 children aged 2–10 years and their parents. Children were randomly assigned to intervention (n = 30) and control (n = 30) groups. Children in the control group were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Vagnoli et al (2010) reported PPIA and clown interventions were more effective in reducing childrens' anxiety than PPIA or oral midazolam and PPIA. Rasti et al (2014) and Jahanpour et al (2017) showed no significant difference between changes in the childrens' anxiety with or without parental presence. Sadeghi et al (2017) found no significant decrease in anxiety with the mYPAS scale and STAI scores showed no differences in childrens' anxiety during induction of anesthesia.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Vagnoli et al (2010) reported PPIA and clown interventions were more effective in reducing childrens' anxiety than PPIA or oral midazolam and PPIA. Rasti et al (2014) and Jahanpour et al (2017) showed no significant difference between changes in the childrens' anxiety with or without parental presence. Sadeghi et al (2017) found no significant decrease in anxiety with the mYPAS scale and STAI scores showed no differences in childrens' anxiety during induction of anesthesia.…”
Section: Discussionmentioning
confidence: 93%
“…Participants were from teaching medical centers in Boushehr. The study population included aged 2-11 years old and were mostly male participants AUTHOR Jahanpour, F., Rasti-Emad-Abadi, R., Naboureh, A., Nasiri, M., & Motamed, N. (2017) Key Findings -There was no significant difference between the intervention and control group regarding parents' anxiety.…”
Section: Appendix A-1mentioning
confidence: 98%
See 2 more Smart Citations
“…แต่ กำรมี ผู ้ ปกครองอยู ่ ด้ วยในระยะน ำสลบต่ อ ควำมวิ ตกกั งวลของเด็ กและควำมสั มพั นธ์ ระหว่ ำงควำมวิ ตกกั งวลของผู ้ ปกครองกั บควำมวิ ตกกั งวล ของเด็ กก่ อนและหลั งกำรดมยำสลบยั งมี ข้ อขั ดแย้ งกั นในผลงำนวิ จั ยที ่ ผ่ ำนมำ(Rasti-Emad-Abadi et al, 2017;Scully, 2012) และยั งไม่ พบควำมสั มพั นธ์ ระหว่ ำงควำมวิ ตกกั งวลของผู ้ ปกครองกั บ ED โดยตรงในเด็ กวั ยก่ อนเรี ยนหลั งดมยำสลบ(Mason, 2017) จำกกำรทบทวนวรรณกรรมข้ำงต้ น พบว่ ำปั จจั ยส ำคั ญที ่ มี ควำมสั มพั นธ์ กั บกำรเกิ ด ED ในเด็ ก เกิ ดได้ จำก 3 ปั จจั ยหลั กคื อ ปั จจั ยส่ วนบุ คคล ได้ แก่ อำยุ ที ่ อยู ่ ในช่ วงวั ยก่ อนเรี ยนและควำมวิ ตกกั งวล ก่ อนกำรผ่ ำตั ด ปั จจั ยด้ ำนพยำธิ สภำพของเด็ กซึ ่ งพบมำกในเด็ กที ่ ป่ วยและต้ องเข้ ำรั บกำรผ่ ำตั ดหู คอ จมู ก และปั จจั ยด้ ำนกำรรั กษำทำงกำรแพทย์ คื อกำรดมยำสลบ พบมำกให้ ผู ้ ป่ วยเด็ กที ่ ได้ รั บยำดมสลบ ชนิ ด sevoflurane ซึ ่ งทำงวิ สั ญญี นิ ยมใช้ เนื ่ องจำกเป็ นยำดมสลบที ่ มี ผลข้ ำงเคี ยงต่ อระบบทำงเดิ น หำยใจและระบบหั วใจและหลอดเลื อดน้ อย แต่ มี ผลข้ ำงเคี ยงต่ อกำรเกิ ด ED เมื ่ อพิ จำรณำจำกปั จจั ย เสี ่ ยงสู งต่ อกำรเกิ ด ED ข้ ำงต้ น พบว่ ำมี ทั ้ งที ่ จั ดกระท ำไม่ ได้ และจั ดกระท ำได้ ส ำหรั บปั จจั ยที ่ จั ด กระท ำได้ และสำมำรถจั ดกระท ำในรู ปแบบที ่ ไม่ ใช้ ยำ เป็ นบทบำทอิ สระของพยำบำลเด็ กภำยใต้ ขอบเขตของวิ ชำชี พกำรพยำบำล คื อ ควำมวิ ตกกั งวลก่ อนผ่ ำตั ด ซึ ่ งเป็ นปั จจั ยส ำคั ญต่ อกำรเกิ ด ED กำรวิ จั ยนี ้ จึ งออกแบบวิ ธี กำรจั ดกำรกั บควำมวิ ตกกั งวลก่ อนกำรผ่ ำตั ด ส ำหรั บปั จจั ยที ่ จั ดกระท ำไม่ ได้ ผู ้ วิ จั ยได้ ค ำนึ งถึ งประโยชน์ ของผลกำรวิ จั ยต่ อกำรน ำไปใช้ (generalization) จึ งมุ ่ งศึ กษำกั บประชำกร ผู ้ ป่ วยเด็ กส่ วนใหญ่ ที ่ พบปั จจั ยเสี ่ ยงสู งต่ อกำรเกิ ด ED คื อ เด็ กวั ยก่ อนเรี ยน เข้ ำรั บกำรผ่ ำตั ดหู คอจมู ก และได้ รั บยำดมสลบชนิ ด sevoflurane โดยก ำหนดเป็ นเกณฑ์ คุ ณสมบั ติ ในกำรคั ดเลื อกกลุ ่ มตั วอย่ ำง ท ำให้ คุ ณลั กษณะของกลุ ่ มตั วอย่ ำงทั ้ งหมดในกำรวิ จั ยมี ปั จจั ยที ่ เกี ่ ยวข้ องต่ อกำรเกิ ด ED เป็ นเอกพั นธ์ กั น (homogeneous) 6.2 งำนวิ จั ยเกี ่ ยวกั บวิ ธี ลดควำมวิ ตกกั งวลก่ อนกำรผ่ ำตั ดในเด็ กวั ยก่ อนเรี ยน จำกกำรทบทวนวรรณกรรมพบงำนวิ จั ยที ่ ใช้ วิ ธี กำรลดควำมวิ ตกกั งวลก่ อนกำรผ่ ำตั ด ด้ วยวิ ธี กำรไม่ ใช้ ยำทั ้ งในรู ปแบบเดี ่ ยวและหลำยรู ปแบบ ด้ วยวิ ธี กำรให้ ควำมรู ้ ก่ อนกำรผ่ ำตั ด กำรสร้ ำง ควำมคุ ้ นเคยกั บสถำนที ่ ก่ อนกำรผ่ ำตั ด และกำรเบี ่ ยงเบนควำมสนใจ ดั งนี ้ 6.2.1 กำรให้ ควำมรู ้ ก่ อนกำรผ่ ำตั ด Kain et al (2007) ได้ ศึ กษำโปรแกรมกำรเตรี ยมผู ้ ป่ วยเด็ กก่ อนกำรผ่ ำตั ดโดย ครอบครั วเป็ นศู นย์ กลำง (the Family-centered preparation ADVANCE preparation) ในเด็ ก อำยุ 2-10 ปี โดยโปรแกรม ฯ ประกอบด้ วย ก่ อนวั นผ่ ำตั ด ผู ้ ปกครองได้ รั บวิ ดี โอจ ำลองเกี ่ ยวกั บกำร ผ่ ำตั ดและดมยำสลบ กำรสอนแนะผู ้ ปกครองเพื ่ อให้ ผู ้ ปกครองได้ สอนเด็ กเกี ่ ยวกั บขั ้ นตอนดมยำสลบ และกำรผ่ ำตั ด เด็ กได้ รั บหน้ ำกำกส ำหรั บกำรดมยำสลบและได้ ตกแต่ งหน้ ำกำกดั งกล่ ำวด้ วยตนเองเพื ่ อ สร้ ำงควำมคุ ้ นเคย และในวั นผ่ ำตั ดเด็ กได้ รั บกำรเบี ่ ยงเบนควำมสนใจด้ วยกล่ องของเล่ น พบว่ ำกลุ ่ มที ่ ได้ รั บโปรแกรม ฯ มี ควำมวิ ตกกั งวลก่ อนกำรผ่ ำตั ดในระยะน ำสลบน้ อยกว่ ำกลุ ่ มที ่ ได้ รั บกำรพยำบำล ตำมปกติ และกลุ ่ มที ่ มี ผู ้ ปกครองอยู ่ ด้ วยในระยะน ำสลบอย่ ำงมี นั ยส ำคั ญทำงสถิ ติ แต่ ไม่ มี ควำมแตกต่ ำง กั บกลุ ่ มที ่ ได้ รั บยำคลำยกั งวลชนิ ดมิ ดำโซแลมก่ อนกำรผ่ ำตั ด และพบว่ ำกลุ ่ มที ่ ได้ รั บโปรแกรมฯ เกิ ด ED น้ อยกว่ ำกลุ ่ มที ่ ได้ รั บกำรพยำบำลตำมปกติ กลุ ่ มที ่ ได้ รั บยำคลำยกั งวลก่ อนกำรผ่ ำตั ด และกลุ ่ มที ่ มี ผู ้ ปกครองอยู ่ ด้ วยในระยะน ำสลบ อย่ ำงมี นั ยส ำคั ญทำงสถิ ติ (10%, 24.2%, 20.7%, 15.5% ตำมล ำดั บ, p = 0.038) Fortier et al (2015) ศึ กษำผลของโปรแกรมกำรเตรี ยมเด็ กและผู ้ ปกครองก่ อนกำร ผ่ ำตั ดผ่ ำนเว็ บไซต์ ที ่ เตรี ยมไว้ (Web-Based Tailored) ในเด็ กอำยุ 2-7 ปี ที ่ เข้ ำรั บกำรผ่ ำตั ดแบบ ผู ้ ป่ วยนอก โดยผู ้ ปกครองจะได้ รั บรหั สกำรเข้ ำถึ งเว็ บไซต์ WebTIPS ทำงจดหมำยเล็ กทรอนิ ค 7 วั น ก่ อนกำรผ่ ำตั ดและสำมำรถเข้ ำถึ งข้ อมู ลได้ ตลอ...…”
unclassified